Knowledge, attitudes and practices of traceability among livestock traders in south-western Nigeria: implications for sustainable livestock industry (2013)
Livestock diseases and other animal health events are a threat to achieving sustainable livestock industry. The knowledge of trace-back and the practice of providing feedback on diseases encountered in slaughtered animals from the abattoir to the farmcan help limit the spread as well as manage potential future incidents of such diseases. We assessed the knowledge, attitudes and practices of 200 willing livestock traders on traceability in Bodija Municipal Abattoir, southwestern Nigeria. The results reveal that the majority of these traders had poor knowledge (79.5 %) and practices (74.0 %) of traceability, though 89.5 % demonstrated good attitudes. While 22.9 % knew that traceability could be an effective means to control diseases, only a lower proportion (9.0 %) knew the health status of the animals being purchased. Though 29.0 % reported the diseases encountered in their animals during slaughter to the farm, only 9.5 % followed up to ensure the farmers take steps at preventing further occurrence of the reported diseases. While age (p =0.000; 0.014) and education (p =0.000; 0.000) were both significant for good knowledge and attitudes, frequency of condemned cases (p =0.000) and length of years in the trade (p =0.004) were, respectively, significant for good knowledge and attitudes with none associated with practice. These poor levels of knowledge and practices of traceability are a threat to sustainable livestock industry, food security and human health; hence, there is an urgent need to institute national feedback mechanism on slaughtered animals in order to strengthen interventions against diseases at farm levels.